2018
DOI: 10.1002/jcp.26470
|View full text |Cite
|
Sign up to set email alerts
|

NEAT1 contributes to breast cancer progression through modulating miR‐448 and ZEB1

Abstract: Breast cancer is a kind of common female cancers. Increasing evidence has exhibited that lncRNAs exert a crucial role in breast cancer. So far, the mechanism of lncRNAs in breast cancer is still not well established. In our current study, we focused on the biological role of lncRNA Nuclear Enriched Abundant Transcript 1 (NEAT1) in breast cancer. We observed that NEAT1 levels were significantly increased in human breast cancer cells including MCF-7, MDA-MB-453, MDA-MB-231, and SKBR3 cells compared to normal mam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
68
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(74 citation statements)
references
References 36 publications
1
68
0
Order By: Relevance
“…Knockdown experiments revealed that NEAT1 accelerated the proliferation, metastasis and glycolysis, while restricting apoptosis of NSCLC cells. The protumor role of NEAT1 is in agreement with published articles, thus, NEAT1 facilitates the development of breast cancer via miR-448 and zinc finger E-box-binding homeobox 1 protein (ZEB1) [30], and NEAT1 contributes to the progression of colorectal cancer via the enzyme probable ATP-dependent RNA helicase DDX5 also known as DEAD box protein 5 or RNA helicase p68 (DDX5) [31]. LncRNAs regulate cellular physiological and pathological processes mainly by functioning as miRNAs sponges [32].…”
Section: Discussionsupporting
confidence: 85%
“…Knockdown experiments revealed that NEAT1 accelerated the proliferation, metastasis and glycolysis, while restricting apoptosis of NSCLC cells. The protumor role of NEAT1 is in agreement with published articles, thus, NEAT1 facilitates the development of breast cancer via miR-448 and zinc finger E-box-binding homeobox 1 protein (ZEB1) [30], and NEAT1 contributes to the progression of colorectal cancer via the enzyme probable ATP-dependent RNA helicase DDX5 also known as DEAD box protein 5 or RNA helicase p68 (DDX5) [31]. LncRNAs regulate cellular physiological and pathological processes mainly by functioning as miRNAs sponges [32].…”
Section: Discussionsupporting
confidence: 85%
“…lncRNAs have a mRNA‐like structure and can function as a ceRNA to competitively bind miRNAs to regulate the expression of mRNAs. For example, the lncRNA nuclear enriched abundant transcript 1 (NEAT1) is significantly increased in breast cancer cells and promotes the progression of breast cancer; NEAT1 was also found to function as a ceRNA to regulate ZEB1 through miR‐448 . The lncRNA small ubiquitin‐like modifier 1 pseudogene 3 (SUMO1P3) is highly expressed in breast cancer tissue samples and is associated with higher staging and worse prognosis .…”
Section: Discussionmentioning
confidence: 99%
“…For example, the lncRNA nuclear enriched abundant transcript 1 (NEAT1) is significantly increased in breast cancer cells and promotes the progression of breast cancer; NEAT1 was also found to function as a ceRNA to regulate ZEB1 through miR-448. 26 The lncRNA small ubiquitin-like modifier 1 pseudogene 3 (SUMO1P3) is highly expressed in breast cancer tissue samples and is associated with higher staging and worse prognosis. 27 The long intergenic non-coding RNA regulator of reprogramming (ROR) is a ceRNA of miR-145 and regulates the expression of ARF6 in triple-negative breast cancer, thus regulating invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, lncRNA HOTAIR may function as a ceRNA to regulate HER2 expression through competition for miR‐331‐3p, thus playing an oncogenic role in gastric pathogenesis . Other studies also showed that ceRNAs were involved in the tumorigenesis of multiple cancer types, including prostate, breast, liver and lung cancers and so on . Although ceRNA research is still in its initial stages, exploration of ceRNA interplay in cancer will provide new insight into mechanisms underlying the pathogenesis of cancers.…”
Section: Introductionmentioning
confidence: 99%